2004
DOI: 10.1002/hipo.10211
|View full text |Cite
|
Sign up to set email alerts
|

Associative recognition in a patient with selective hippocampal lesions and relatively normal item recognition

Abstract: Previous work (Mayes et al., Hippocampus 12:325-340, 2002) found that patient YR, who suffered a selective bilateral lesion to the hippocampus in 1986, showed relatively preserved verbal and visual item recognition memory in the face of clearly impaired verbal and visual recall. In this study, we found that YR's Yes/No as well as forced-choice recognition of both intra-item associations and associations between items of the same kind was as well preserved as her item recognition memory. In contrast, YR was cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
197
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(213 citation statements)
references
References 61 publications
13
197
3
Order By: Relevance
“…Hypoxic patients showed intact familiarity, whereas patients with more extensive medial temporal damage showed impaired familiarity, consonant with the view that the contribution of the hippocampus to familiarity is minimal. Additional evidence likewise indicates that patients with damage restricted to the hippocampus can show relatively preserved familiarity with impaired recollection (Aggleton et al, 2005;Baddeley, Vargha-Khadem, & Mishkin, 2001;Bastin et al, 2004;Holdstock et al, 2002;Mayes et al, 2004). Studies that have assessed recognition in patients with extensive medial temporal damage have found that these patients generally exhibited recognition deficits in both recollection and familiarity (Giovanello & Verfaellie, 2001;Knowlton & Squire, 1995).…”
mentioning
confidence: 99%
“…Hypoxic patients showed intact familiarity, whereas patients with more extensive medial temporal damage showed impaired familiarity, consonant with the view that the contribution of the hippocampus to familiarity is minimal. Additional evidence likewise indicates that patients with damage restricted to the hippocampus can show relatively preserved familiarity with impaired recollection (Aggleton et al, 2005;Baddeley, Vargha-Khadem, & Mishkin, 2001;Bastin et al, 2004;Holdstock et al, 2002;Mayes et al, 2004). Studies that have assessed recognition in patients with extensive medial temporal damage have found that these patients generally exhibited recognition deficits in both recollection and familiarity (Giovanello & Verfaellie, 2001;Knowlton & Squire, 1995).…”
mentioning
confidence: 99%
“…Evidence for the dissociability of relational and item/non-relational recognition stems from fMRI studies of differential hippocampus vs. perirhinal cortex/anterior parahippocampal cortex activations associated with the two types of memory (Pihlajamaki et al 2004;Kohler et al 2005;Daselaar et al 2006;Montaldi et al 2006). Studies of patients with hippocampal lesions have as yet not yielded a clear picture with respect to the dissociability of relational and non-relational memory Manns et al 2003;Mayes et al 2004;Wixted and Squire 2004;Wais et al 2006;Wixted 2007). Interestingly, single-unit recordings in human epilepsy patients demonstrated that hippocampal neurons show a familiarity response in the absence of successful recollection, but notably also in the absence of successful non-relational recognition (Rutishauser et al 2006).…”
mentioning
confidence: 99%
“…The perirhinal cortex was shown to be involved in the perceptual analysis of single items and in binding of individual stimulus features into a coherent representation of an object, which requires perceptual and mnemonic competence (Bussey et al 2002;Buckley 2005;Bussey and Saksida 2005). It may support relational processing under some circumstances, such as unitizing two features of the same kind to one single item or merged unity representation, but not spatiotemporal relational associations (Norman and O'Reilly 2003;Mayes et al 2004;Jager et al 2006). The hippocampus, on the other hand, mediates associations of the same kind such as object-object associations (Kesner and Hopkins 2006).…”
mentioning
confidence: 99%
“…Damage to this system causes deficits in spatial memory and in memory for complex relational information that typifies memory for autobiographical episodes, but spares recognition based only on familiarity (Aggleton et al, 2000;Holdstock et al, 2002a;Mayes et al, 2002Mayes et al, , 2004D. Moscovitch & McAndrews, 2002;Yonelinas, 2002;Yonelinas et al, 2002).…”
Section: The Relevance Of the Neuroanatomical Components Of The Mediamentioning
confidence: 99%
“…A number of studies showed that recollection was disproportionately impaired following lesions that included the hippocampus, whereas familiarity was relatively spared (Holdstock et al, 2002a, b;Mayes et al, 2003Mayes et al, , 2004D. Moscovitch & McAndrews, 2000;Yonelinas et al, 2002).…”
Section: Parallels Between Anterograde and Retrograde Memory: A Commomentioning
confidence: 99%